Lewis Acid Catalyzed Domino Ring-Opening Cyclization of Azetidines with Alkynes: Synthesis of Tetrahydropyridines - Shukla, Dipti; Singh, Shishir; Sharma, Amit Kumar; Singh, Bharat; Bhattacharyya, Aditya; Talukdar, Ranadeep; Ghorai, Manas K. (Synlett, 2024)
A simple strategy for the synthesis of a variety of tetrahydropyridines in good to excellent yields via a Cu(OTf)2 catalyzed quaternary ammonium salt mediated ring-opening of activated azetidines followed by cyclization with alkynes in a domino ring-opening cyclization (DROC) is described. The formation of the products has been explained by an SN2-type ring-opening of azetidines with alkynes.
Keywords: azetidine; alkyne; SN2-type ring-opening; DROC